Efektivitas Pelatihan Peer Educator dalam Pencegahan Perkawinan Anak - Nurhayati, Siti Rohmah; Adira, Nesya; Karsiyati; Reginasari, Annisa; Salsabila, Hasna; Anisa, Yusti Setya (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2026)
This Community Service (PkM) program aims to enhance participants’ knowledge and skills through intervention-based training, enabling them to educate their peers about the prevention of child marriage. The program was implemented in Belitung Regency, involving 31 participants from several schools. The program’s effectiveness was evaluated using a one-group pretest–posttest design with paired-sample t-tests. The results of the paired-sample t-test showed an increase in the mean pretest score (M = 17.9, SD = 4.51) and posttest score (M = 23.5, SD = 3.62), with a mean difference of 5.65 points—a statistically significant difference: t(30) = –7.18, p < .001. A very large effect size (Cohen’s d = 1.29) indicates that the training had a substantial impact on participants’ knowledge. The study’s findings underscore the importance of practical training-based interventions in fostering children’s capacity as peer educators, while also providing recommendations for broader implementation in other regions with similar characteristics.